Charge transfer dynamics of 9-arylcarbazole studied by femtosecond transient absorption spectroscopy - Takamoto, Kazuya (2020)
In chemistry it is important to understand reaction mechanisms in solutions at a molecular level because most chemical reactions occur in solutions. Intramolecular charge transfer (ICT) in solutions is one of the most basic reactions, and the reaction mechanism of ICT is influenced by not only solute-solvent interactions but also geometrical change of solute molecule. 3,6-Bis(dimethylamino)-9-(4-cyanophenyl)carbazole (BANCC, Figure 1(a)) consists of an electron donor of the carbazole unit and an acceptor of the cyanophenyl unit, which are connected by a single bond[1]. In order to elucidate the ICT reaction mechanism of BANCC, we performed real time observation of the reaction process in various organic solvents by femtosecond transient absorption (TA) spectroscopy.